HUBUNGAN DURASI BERMAIN VIDIO GAME DENGAN KETAJAMAN PENGLIHATAN PADA ANAK SEKOLAH DI SDN 007 PULAU BIRANDANG - RINDA FITHRIYANA (Jurnal Ners, 2019)
Vision is one of the most important factors in all aspects of life including in the educational process. Although its function for human life is very important, but often eye health is less noticed, so many diseases that attack the eye are not treated properly and cause vision problems. In 2013 the prevalence of visual acuity disorders in school-age children in Indonesia increased due to activities in front of the electronic media screen such as playing video games. The purpose of this study was to determine the relationship of the duration of playing video games with visual acuity in school children at SDN 007 Birandang Island in 2017. The design of this study was analytic with cross sectional design. The population in this study were all students in grade V and VI SDN 007 Birandang Island, amounting to 85 people, using a sampling technique with total sampling. The results showed that the majority of respondents played video games> 2 hours (60%), the majority of respondents had abnormal vision as many as 44 people (51.8%). The results showed that there is a relationship between the duration of playing video games with visual acuity in school children at SDN 007 Birandang Island in 2017. It is hoped that the school can create a new program in the form of extracurricular activities that are made as attractive as possible to divert student activities from playing video games.